Generalized erythematous–violaceous plaques in a patient with a history of dyslipidemia. (3rd March 2013) - Hernández, Noelia; Peñate, Yeray; Borrego, Leopoldo
<x xml:space="preserve">Abstract</x> What is your diagnosis?